PEMBELAJARAN PEMAHAMAN KONSEP IPA SISWA KELAS IV SD PADA MATERI PERAMBATAN BUNYI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION - Lilis, Lilis; Kelana, Jajang Bayu (IKIP Siliwangi, 2021)
The purpose of this study was to determine the scenario and implementation of learning science concept understanding for fourth-grade elementary school students on the material of sound propagation using the cooperative model type investigation group. observation, it turns out that the understanding of the fourth-grade science concept in elementary school is still low. This is the case the researcher uses the cooperative model type group investigation as a solution to improve students' understanding of science concepts to be better. The research method used by researchers is descriptive qualitative method, this is so the researcher can explain the efforts made by the teacher in improving the quality of learning, especially in the material of sound propagation. The subjects in this study were students of grade IV in a state school in West Bandung Regency, which amounted to 30 students, consisting of 15 male students and 15 female students. Based on the results obtained during the implementation of the learning process, the results of the increase in the average score of the science concept understanding test results were 100%. It can be concluded that the results of the study indicate that there is a significant increase.